Coral Reef Cover Conditions in the Kayaking Tourism Area at Ujung Genteng Beach in August 2025 - Rabbani, Muhammad Ridho Fazli; Iman, Nuzulul Alamul; Nurshafa, Aziza Nabila; Salsabila, Alisha (Jurnal Biologi Tropis, 2025)
Coral reefs are vital marine ecosystems that support high biodiversity and provide essential ecological services, yet many are experiencing rapid degradation due to increasing human pressures. This study assessed the condition of live coral cover and evaluated reef health within the kayak tourism area of Ujung Genteng Beach, West Java. Field surveys were conducted in August 2025 across five stations using the Line Intercept Transect (LIT) and Underwater Visual Census (UVC) methods. Results showed that non-biological substrates such as sand (45.38–79.90%) and rubble (6.70–27.78%) dominated the benthic composition, while live coral cover remained low at 3.24–16.48%, with an overall average of 9.19%. Based on the Indonesian Ministry of Environment Decree No. 4/2001, the reef condition is categorized as poor. These findings indicate significant ecological degradation likely linked to both environmental stressors and tourism-related disturbances. The study concludes that effective habitat protection, zoning arrangements, and sustainable marine tourism practices are urgently needed to enhance coral resilience and prevent further decline.